Processos e subprocessos do pensamento matemático avançado identificados nas habilidades do pensamento computacional - Okamoto, Mariana Maestripieri (2021)
Wing's computational thinking, the central object of this research, has been discussed in curriculum guidance documents aimed at Brazilian education, such as the BNCC and the reference in technology and computing elaborated by the CIEB, and when studying Dreyfus advanced mathematical thinking, we propose to investigate the processes and subprocesses of advanced mathematical thinking present in computational thinking skills. We use theoretical assumptions of computational thinking according to Wing. Framing itself as a qualitative research, this investigation used the methodology of content analysis assumptions according to Bardin to analyze 20 theses and dissertations from Mathematics Education programs in Brazil that had computational thinking as theoretical support, seeking the relationship with the processes and Subprocesses of Advanced Mathematical Thinking: Abstract, Represent, Generalize, Synthesize, Visualize, Model and Conjecture. This research allowed us to conclude that the processes and subprocesses of advanced mathematical thinking: abstracting, representing, generalizing, visualizing and modeling are present in computational thinking skills, whereas the subprocesses and processes of conjecturing and synthesizing are not identified with connection or meaning in the skills of computational thinking of our corpus of analytics. The processes or subprocesses of advanced mathematical thinking, visualizing, representing, abstracting, and modeling are interconnected, that is, we find that they occur simultaneously most of the time in the development of computational thinking